2001
DOI: 10.1093/hcr/27.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Empirical support for the gender-as-culture hypothesis. An intercultural analysis of male/female language differences

Abstract: This investigation provided a test of the gender-as-culture, or "two cultures," hypothesis proposed by Maltz and Borker (1982) to explain male/female differences in language use. Analysis of previous empirical investigations located 16 language features that had consistently been shown to indicate communicator gender and these were tested within the framework of the four dimensions of intercultural style proposed by Gudykunst and Ting-Toomey (1988): direct versus indirect, succinct versus elaborate, personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
157
2
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(178 citation statements)
references
References 20 publications
10
157
2
9
Order By: Relevance
“…Male learners' preference for the pronoun you, seems to position them higher than the reader; evoking a sense of authority and dominance. This is a communication style often associated with men, who, according to researchers, use language to enhance social dominance (Leaper 1991, Mulac, Bradac & Gibbons 2001. On the contrary, female writers' preference for the inclusive we builds a rapport with the reader and puts them at one with the reader.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male learners' preference for the pronoun you, seems to position them higher than the reader; evoking a sense of authority and dominance. This is a communication style often associated with men, who, according to researchers, use language to enhance social dominance (Leaper 1991, Mulac, Bradac & Gibbons 2001. On the contrary, female writers' preference for the inclusive we builds a rapport with the reader and puts them at one with the reader.…”
Section: Discussionmentioning
confidence: 99%
“…The former has the tendency to transmit a sense of togetherness and cooperation by equating themselves in their arguments (Mason 1994), while the latter seems to project an aura of dominance and authority by separating themselves from the reader (Leaper 1991, Mulac, Bradac & Gibbons 2001 As summarised in Table 5, only four key hedges were most often employed by learners, and they include should, would, may and most. Asian learners in general are very cautious and indirect in expressing their opinions (Ahmad 1995); thus, modals such as should, would and may would be common occurrences in their writing.…”
Section: Dia005m Uitmmentioning
confidence: 99%
“…Mehl and Pennebaker (2003) found that men use a lot of articles in their language, they employ a lot of swear words, prefer to use large and long words (6 characters and above) and prefer to show their anger instead of hiding it. Mulac, Bradac, and Gibbons (2001) reviewed and analysed more than 30 studies, and proposed a list of systematic ways of distinguishing language features according to gender preferences. Some details are given as follows:…”
Section: Exploring Men's Speechmentioning
confidence: 99%
“…Sample 6 and 11 turned out as sarcastic jokes. Some elements of directive language (Mulac, Bradac & Gibbons 2001) were traced in Sample 3 (in Table 8) and Sample 8. In Sample 3, Participant 9 (P9) insisted on getting the information from his friend while Sample 8 shows how Participant 20 (P20) insisted his friend to trust his decision and action.…”
mentioning
confidence: 99%
“…That the context of the data source can influence gender discriminability is not evidence against the "gender as culture" hypothesis (see [5]); however, this depends on the granularity of context circumscription. Where reversal of a gender effect is conditioned on context, it could be that the context has culturally salient properties.…”
Section: Introductionmentioning
confidence: 99%